PENGARUH LINGKUNGAN KERJA, KOMPETENSI, KEPUASAN KERJA DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN PT. MUTIARA SAWIT SELUMA - Ilahi, Muhammad Ridho; Bahrun, Khairul (UM. Bengkulu, 2025)
This study aims to determine the effect of work environment, competence, job satisfaction, and organizational commitment on employee performance of PT Mutiara Sawit Seluma. This type of research is quantitative research with a descriptive approach. The population of this study were all employees of PT Mutiara Sawit Seluma. The number of research samples was 63 people. Data collection was carried out using a questionnaire. Data analysis techniques using multiple linear regression analysis techniques. The results of data analysis show that partially the work environment has a positive and significant effect on performance, competence has a positive and significant effect on performance, job satisfaction has a positive and significant effect on performance. and organizational commitment has a positive and significant effect on performance. It is recommended to the management of PT. Mutiara Sawit Seluma to be able to improve employee performance by creating a positive work environment, increasing employee competence, increasing employee job satisfaction, and increasing employee organizational commitment.Keywords: Performance, work environment, competence, job satisfaction, organizational commitment